Proposal on Provincial Self Governance Model of Thailand (Journal of Governance and Development (JGD), 2014)
Although Thailand has tried to develop decentralization movements, it cannot reach the ideological goal which is delivering of administrative power to people for self governance. This power continues to be held by the elite groups in the central government. This study presents the details of unsuccessful decentralization movements and the causes for their failures. It will furthermore propose an innovative idea to promote decentralization through the concept of â€œProvincial Self-Governanceâ€, aiming to promote and foster citizen engagement instead of people participating in local administrations. This article would like to present how to apply this concept through studying the succession of making â€˜Amnajcharoen People Charterâ€™. The study found that this charter was developed by 4 major factors including constitution, the outside province organizations, the inside province organizations and the non-government organizations and civil society organizations in the area. There are 2 key success factors of making the people charter including as the succession in development partnership building and the development network management.